Rapid hyperspectral imaging in the mid-infrared - Kröger-Lui, Niels; Egl, Alexander; Engel, Maria; Gretz, Norbert; Isensee, Katharina; Herpich, Iris; Neudecker, Sabine; Pucci, Annemarie; Schönhals, Arthur; Petrich, Wolfgang (Biomedical vibrational spectroscopy VI, 2014)
Despite the successes of mid-infrared hyperspectral imaging in a research environment, progress in the migration of technology into the day-to-day clinical application is slow. Clinical acceptance may be improved if the spectroscopy would be faster and the infrared microscopes available at lower cost. Here we present first results of a fast, multi-scale mid-infrared microscopy setup which allows for the investigation of 10.6×11.7 mm2 and 2.8×3.1mm2 fields of view with a resolution of 23.0+/-3.5 μm and 9.4+/-1.8 μm, respectively. Tunable quantum cascade lasers in the wavenumber ranges of 1030-1090 cm-1 and 1160-1320 cm-1 serve as light sources. A vapor cell is used as a frequency reference during the rapid scanning. As far as the imaging is concerned, it is the high spectral power density of the quantum cascade laser which enables the use of a microbolometer array while still obtaining reasonable signal-to-noise ratios on each pixel. Hyperspectral images are taken in times which can be as low as 52s for the overall image acquisition including referencing.
Gesehen am 11.12.2020